Some discussions on equipartition theorem - Pulinchery, Prasanth; Perayil, Reshma; Pothyiodath, Nishanth; Aravind, Aravind; Murkoth, Udayanandan Kandoth (Momentum: Physics Education Journal, 2023)
During the development of physics, we can see that the Equipartition Theorem (EPT) has been redefined many times. In this paper, we start with the description of the historical development of the theorem along with the various definitions given by different scientists. Then we found the expressions for classical, quantum, and discrete energy systems and redefined EPT.